Pengaruh Citra Merek, Kualitas Produk, Persepsi Harga, Promosi Dan Label Halal Terhadap Kepuasan Pelanggan Ms Glow Pada Rentang Usia 18-25 Tahun Di Kota Malang - Ashifa Maharani; Rois Arifin; M. Khoirul Anwarodin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2021)
Abstract The purpose of this study is to see how brand image, product quality, pricing perception, promotion, and the halal label affect Ms Glow's customer happiness in Malang, Indonesia. This study is an example of explanatory research using a quantitative approach to investigate the relationship between variables. The participants in this study were Malang-based female Ms Glow product customers between the ages of 18 and 25. A sample will be determined from this population using Malhotra's formula approach, yielding a sample of 95 samples. Instrument testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, and coefficient of determination tests were used in this study's data analysis. The results demonstrated that there was a simultaneous influence between the factors of brand image, product quality, price perception, promotion, and halal label on Ms Glow's customer satisfaction in the age range of 18-25 years in Malang City, based on the results of the t-test and f-test. The variables brand image (X1), product quality (X2), pricing perception (X3), promotion (X4), and halal label (X5) can explain 78.1 percent of the dependent variable, namely consumer satisfaction, whereas other variables outside the study model can explain 21.9 percent. Keywords: Customer Satisfaction, Brand Image, Product Quality, Price Perception, Promotion, Halal Label